Transformation of Red Chilli Variety Cillibangi-2 (Capsicum annum L.) With cDNA of Cucumber Mosaic Virus Coat Protein Gene by Direct Uptake - Ahmad I.B.; A.M. Mahir; A. Zaiton; Hanina Mohd Noor (Asian Network for Scientific Information, 2024)
Volume: 5 | Issue: 6